Effectiveness of learning transfer in national dual training system (NDTS) - Ahmad, Azmi (2011)
Learning transfer is the ultimate goal of any training programme. The new Malaysian skills training is based on the dual learning principle in which trainees alternate between attending theoretical classes in the skills training institute and receiving onthe-job training at worksite. This new paradigm of skills training is better known as